2022
DOI: 10.1186/s12887-022-03466-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth improvement following antiretroviral therapy initiation in children with perinatally-acquired HIV diagnosed in older childhood in Zimbabwe: a prospective cohort study

Abstract: Background Children who initiate antiretroviral therapy (ART) before age 5 years can recover height and weight compared to uninfected peers, but growth outcomes are unknown for children initiating ART at older ages. We investigated factors associated with growth failure at ART initiation and modelled growth by age on ART. Methods We conducted secondary analysis of cohort of children aged 6–15 years late-diagnosed with HIV in Harare, Zimbabwe, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Despite good immunological control of HIV infection, stunting remains a major issue in these HIV-infected adolescents (21). Since HIV-infected infants are now beginning treatment early, new studies have shown that stunting is not as prevalent as in this study, where ART was not started in infancy (12).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Despite good immunological control of HIV infection, stunting remains a major issue in these HIV-infected adolescents (21). Since HIV-infected infants are now beginning treatment early, new studies have shown that stunting is not as prevalent as in this study, where ART was not started in infancy (12).…”
Section: Discussionmentioning
confidence: 52%
“…A study performed on Zimbabwean and Ugandan HIV-infected adolescents to assess the age of attaining Tanner stages with reference to the age of ART initiation showed that the mean age of ART initiation was 9.4 years and that delaying ART initiation signi cantly delayed pubertal development and menarche (11). In another study performed in Zimbabwe, stunting and underweight were more prevalent at ART initiation among late-diagnosed adolescents, especially boys with perinatally acquired HIV infection, and those diagnosed late were particularly at risk of growth failure in puberty (12).…”
Section: Introductionmentioning
confidence: 99%